A Study for Energy Consumption patterns and Carbon Dioxide emissions for Residential Building in Dubai - AL SHEHHI, FATEMA AHMED (2011)
The climate is changing and recent years show that the earth is warming up, sea level is rising and carbon dioxide (CO2) increasing as well. Human activities are considered as part of climate change due to the amounts of greenhouse gases emitted by these activities to the atmosphere. The Environmental Protection Agency (EPA) concludes that “Since the beginning of the industrial revolution, atmospheric concentrations of carbon dioxide have increased nearly 30%...and nitrous oxide…risen by about 15%. These increases have enhanced the heat-trapping capability of the earth’s atmosphere.” Globally, energy consumption increased and as per IEA (2010), the total world energy used by sector is as follows: 28% for the industry sector, 27% for the transport sector, and 36% for the residential and service sector. Locally, as per the Annual Statistical Report for Electricity and Water (2010), the total gross generating capacity increased by 5967 MW from 2004 to 2009. Statistically, studies for The Dubai Statistics Center (2009) have indicated that most energy consumption is located in the Commercial sector. Mainly, it accounts for 43% of the overall Dubai energy consumption, being the rest divided between the Residential sector (30%), Industry (9%), and another type (18%). Moreover, research by The UAE Ecological Footprint Initiative Summary Report 2007-2010, 2011) shows that the household sector was the major contributor in the UAE’s Footprint which is responsible for 57%. The purpose of this research is to investigate energy consumption and carbon dioxide emissions from the residential sector in Dubai. Also, to find out the influence factors on the energy consumption for the residential buildings. The investigated residences were located in eight different locations along the Emirate of Dubai. Questionnaire survey methodology is to be used for this investigation and the questionnaire survey is structured in a way that is to be used as data for the household profile in Dubai in particular and in UAE in general. It's revealed building characteristics and household characteristics in the energy use in addition to the influence of households’ lifestyle on energy consumption. The questionnaire also covered white goods items, home entertainment items, computer and peripheral items, air-conditioners, and lighting. More than 200 hard copy questionnaires were distributed to the selected area, in addition to the electronic copy distributed to relatives, friends, Colleagues, and others. Questionnaire results were based on surveys of 95 households for different types of residences; villas, detached houses, Arabic houses, and apartments in different locations. The research result outlines the key drivers that impacts on energy consumption. According to the results; Major electricity-consuming items were air-conditioners, lighting, and refrigerators. Furthermore, consumers' behavior is the most important issue of energy consumption. This impacts of that energy which is particularly fossil-fuel-generated electricity on carbon released to the atmosphere. The dissection report ends with a section for recommendation of efforts, such as detailed survey, policy and regulation, intended to influence building energy use. Recommended courses of action from BUID to the residential leaders, students. The holistic and integrated approach to the research objective, guided by Systems thinking and ecological design, capacities actors at three different levels to pro-Actively implement end-use energy efficiency.